The Function of Myth within Noahs and Uta-napishtims Stories: A Comparative Analysis of the Deluge in Genesis 6-9 and the Epic of Gilgamesh Tablet XI - Natan Setiawan Gultom (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2019)
Ancient stories which depict similarities in their details of the narrative can be found in various cultures and civilization. Two stories that look similar to each other are the ancient text of The Epic of Gilgamesh and the Biblical book of Genesis. The deluge, observed in both stories, seems to have an impact towards the ever-famous discussion of which story is more authentic. This article gives a comparative analysis of both stories. The aim of this study does not concern with such discussions, rather arguing how both stories, after investigating the similarities and differences, generates a mythwhich may come from a factual historyfor their respective people and culture, preserving cultural history, rational conducts, and religious rituals of each culture concerned.Keywords: Genesis, Epic of Gilgamesh, Noah, Utanapishtim, Ancient Text, Mythology